Building Better Homes Government Strategies for Promoting Innovation in Housing - Hassell, Scott (RAND Corporation, 2003)
This report examines the structure, characteristics, and motivations of major participants in the housing industry to explore how innovation might be accelerated. It identifies options and strategies for the federal government to consider as it attempts to further advance innovation in housing to make homes more affordable, durable, and safe. Innovation in housing would provide benefits to a broad range of participants, including homebuilders, manufacturers, insurers, regulators, and homeowners.